Analisis Tanggung Jawab Perdata atas Kerugian yang Timbul pada Tahap Pra-Kontraktual dalam Hukum Perjanjian - Maria Salsa Syakira (Jurnal Hukum Lex Generalis, 2026)
This study examines civil liability for losses arising during the pre-contractual stage in Indonesian contract law. The pre-contractual stage is the initial phase preceding the formation of a contract, encompassing the processes of negotiation, offer, and exchange of information between the parties. Although it does not yet give rise to a legally binding relationship, interactions during this stage have the potential to cause losses if one of the parties fails to act in good faith. The resulting losses may include negotiation costs, lost business opportunities, or losses resulting from misleading information (reliance loss). This study employs a normative approach by examining provisions in the Civil Code and relevant legal doctrines. The findings indicate that civil liability during the pre-contractual stage can be grounded in the concept of tort as stipulated in Article 1365 of the Civil Code and supported by the doctrine of culpa in contrahendo. Thus, the law provides protection not only after the contract is formed but also from the negotiation stage onwards